Viabilidade econômica da implantação de agricultura de precisão na cultura do arroz irrigado em Cachoeira do Sul/RS - Santos, Lucas Bauer dos (2014)
Due to the high cost of production, some farmers have abandoned their activities and invested in other, with the factors mismanagement of your business and the lack of specific technologies to its development, coupled with lack of a study that points the technical and economic feasibility insertion of these technologies. This study's main objective is to point out the technical / economic feasibility of the implementation of the Precision Farming System (PA) in the rice crop planted in the pre-germinated system in the city of Cachoeira do Sul/RS, without the need for machinery acquisition specific nor skilled labor, with simple techniques that can be performed by the manufacturer or the technician who has knowledge in AP. An experimental area of 42 hectares has been evaluated with sampling of 1 hectare grids and application of nutrients to variable rate through physical demarcation (banners) of management zones. Plants were harvested mechanically and productivity was inferred through the manual harvest estimation methods that have proven effective. The cost of production in the area of traditional cultivation system was R$ 5,412.21 ha-1, with a revenue of R$ 8,457.88 ha-1 and in precision agriculture cultivation system R$ 5,241.01 ha-1, with a revenue of R$ 8,401.40 ha-1, with the PA system increased profitability (R$ 114.72 ha-1) compared to the traditional system, showing the technical feasibility / economic / environmental deployment the Precision Farming system at the study site.